2020
DOI: 10.3390/vaccines8030451
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Encephalitis Virus: A Quest for Better Vaccines against a Virus on the Rise

Abstract: Tick-borne encephalitis virus (TBEV), a member of the family Flaviviridae, is one of the most important tick-transmitted viruses in Europe and Asia. Being a neurotropic virus, TBEV causes infection of the central nervous system, leading to various (permanent) neurological disorders summarized as tick-borne encephalitis (TBE). The incidence of TBE cases has increased due to the expansion of TBEV and its vectors. Since antiviral treatment is lacking, vaccination against TBEV is the most important protective meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 248 publications
(453 reference statements)
0
53
0
Order By: Relevance
“…Several VLP vaccine candidates have been developed employing the E protein as antigen [11,12]. Flavivirus E protein comprises the majority of the virion structure and surface [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several VLP vaccine candidates have been developed employing the E protein as antigen [11,12]. Flavivirus E protein comprises the majority of the virion structure and surface [13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite SARS-CoV-2 being a primarily respiratory pathogen, viral antigens were also found in the brain parenchyma and in single cases in the cerebrospinal fluid (CSF) of severely affected COVID-19 patients [ 268 , 269 , 270 ]. Song et al [ 271 ] demonstrated neuroinvasion of SARS-CoV-2 in human brain organoids, ACE2-expressing mice, and in human post-mortem tissues. Despite neurological symptoms that are associated with COVID-19, as well as long COVID-19, SARS-CoV-2 mostly is a respiratory pathogen and only rarely causes neurotropic infections.…”
Section: Innovative Tlr Agonist Mediated Intervention Strategies and Enhancement Of Vaccine Responses Against Neurotropic Virus Infectionmentioning
confidence: 99%
“…Flavivirus infections are of global importance for human health and pose increasing threats, as illustrated by the spread of dengue (DEN), Zika, West Nile, and tick-borne encephalitis virus (TBE) viruses (reviewed in [ 1 , 2 ]). These pathogens are transmitted to humans by specific arthropod vectors, either mosquitoes (dengue, Zika, West Nile, yellow fever, and Japanese encephalitis viruses) or ticks (TBE virus).…”
Section: Introductionmentioning
confidence: 99%